Gender-aware inclusive value chain: A theoretical perspective - Kini, Janvier (Frontiers in Sustainable Food Systems, 2022)
Achieving SDG5 requires an analytical and practical framework enabling a win–win participation of women with poor resources in gender-blind societies. Women with poor resources are mostly excluded from formal economic systems and face gender inequalities. In agricultural and food value chains, women are not equally included as men in highly attractive value chains, so they end up engaging in informal (less lucrative) agri-food activities alongside the value chains. However, the existing literature fails to design an adequate framework that efficiently addresses gender inequality and the poverty conditions of women in low-income countries, mostly gender-blind. This study contributes to filling this knowledge gap by proposing a gender-aware inclusive value chain from a theoretical perspective. For this purpose, we conducted a deep and extensive state-of-the-art study on value chain development and strategies over the past three decades. Two main types of value chains are drawn from this literature review: (1) conventional value chains, mainly exclusive or adverse, including the bottom of the pyramid populations and gender-blind; and (2) gender-aware value chains mostly focus on value chains that are controlled by women. Hence, the paper proposes a third type of value chains inspired by the Foucauldian perspective of human being: gender-aware inclusive value chain (GAIVC). This perspective considers a value chain similar to the human body in its functioning because the human body is composed of different organs that are autonomous but complementary to each other. GAIVC is also composed of different elements (actors/stakeholders, farms, storage, infrastructure, and so on) that should be complementary and non-competitive. From this perspective, it provides more opportunities for poor resource women to evolve into a non-discriminatory environment based on gender. It also breaks down the power relations between the chain actors, as they have to cooperate and avoid the chain from collapsing from within and outside threats. In this way, the sustainability of value chains is guaranteed, and all actors involved receive fair rewards from chain participation.